Frontiers in Fine-Scale in situ Studies: Opportunities During the SWOT Fast Sampling Phase - d’Ovidio, Francesco; Pascual, Ananda; Wang, Jinbo; Doglioli, Andrea M.; Jing, Zhao; Moreau, Sebastien; Grégori, Gérald; Swart, Sebastiaan; Speich, Sabrina; Cyr, Frédéric; Legresy, Benoit; Chao, Yi; et al. (Frontiers in Marine Science, 2019)
Conceived as a major new tool for climate studies, the Surface Water and Ocean Topography (SWOT) satellite mission will launch in late 2021 and can retrieve the dynamics of the ocean upper layer at an unprecedented resolution of a few kilometers. During the calibration and validation (CalVal) phase in 2022, the satellite will be in a 1-day-repeat fast sampling orbit with enhanced temporal resolution but sacrificing the spatial coverage. This is an ideal opportunity - unique for many years to come - for coordinating in-situ experiments during the same period for a focused study of the find scale dynamics and their broader rolesin the Earth system. Key questions to be addressed include the role of the fine scales on the ocean energy budget, the connection between their surface and internal dynamics, their impact on plankton diversity, and their biophysical dynamics at the ice margin.